2014
DOI: 10.1016/j.actatropica.2014.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of midgut microflora and dengue virus impact on life history traits in Aedes aegypti

Abstract: Significant morbidity and potential mortality following dengue virus infection is a re-emerging global health problem. Due to the limited effectiveness of current disease control methods, mosquito biologists have been searching for new methods of controlling dengue transmission. While much effort has concentrated on determining genetic aspects to vector competence, paratransgenetic approaches could also uncover novel vector control strategies. The interactions of mosquito midgut microflora and pathogens may pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…In A. aegypti, the microbiota in the mosquito has been reported to influence the susceptibility to infection to arboviruses [13,15,16]. For example, DENV replication has been reported to be affected by gut bacteria [17,18] which exert antiviral activity through mechanisms not completely understood [13,[19][20][21], but that may be indirectly associated to innate antiviral responses and antimicrobial peptides by the gut microbiota [17]. Studies on the microbiome reinforce the great potential for the development of microbial-based strategies to control vector-borne pathogens [13].…”
Section: Introductionmentioning
confidence: 99%
“…In A. aegypti, the microbiota in the mosquito has been reported to influence the susceptibility to infection to arboviruses [13,15,16]. For example, DENV replication has been reported to be affected by gut bacteria [17,18] which exert antiviral activity through mechanisms not completely understood [13,[19][20][21], but that may be indirectly associated to innate antiviral responses and antimicrobial peptides by the gut microbiota [17]. Studies on the microbiome reinforce the great potential for the development of microbial-based strategies to control vector-borne pathogens [13].…”
Section: Introductionmentioning
confidence: 99%
“…While previously assumed to be mostly benign (Hardy et al 1983), vector responses to pathogens are governed by the same constraints as host/parasite relationships; balancing the need to invest in an immune response against the costs of any pathogen induced virulence (McKean and Lazzaro 2011). Pathogen infections can negatively affect vector fitness but the magnitude of the impact seems to vary depending on mosquito genotype (Maciel-de-Freitas et al 2011;Carrington et al 2013;Sylvestre et al 2013;Hill et al 2014) and interactions with the environment (Ferguson and Read 2002;Sangare et al 2014). Our growing appreciation for the diverse and specialized immune response of insects (Sim et al 2014), typically revealed by transcriptional profiling (Oduol et al 2000;Bonizzoni et al 2012), offers an independent means to assess the nature of a vector's energetic investment in pathogen interactions (Ye et al 2009).…”
mentioning
confidence: 99%
“…Kang et al [172] found that larval-stage crowding and nutritional limitation led to lower survival rates until pupation, lower blood feeding success, slower development, smaller adult body size, and lower susceptibility to DENV-2 infection. Four studies examined a variety of blood meal characteristics on arboviral infection rate [122,123,147,173]. Fresh Zika-infected blood meal was associated with significantly higher infection rates than frozen Zika-infected blood meal [122].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Zika-infected whole blood meal was associated with significantly higher infection rates than Zika-infected protein meal [123]. Hill et al [147] studied the impact of antibiotics on dengue infection rate and mosquito fertility, and found no significant association in Ae. aegypti .…”
Section: Resultsmentioning
confidence: 99%